Okužba s SARS-CoV-2 pri otrocih z oslabljeno imunostjo - Stojnić, Tatjana (Obzornik zdravstvene nege, 2026)
Introduction: Anyone can become infected with the SARS-CoV-2 virus. However, children with weakened immunity are at greater risk of developing various infections, including COVID-19. It is important to treat these children promptly, especially those with additional comorbidities. The aim of this literature review was to investigate the course of COVID-19 in immunocompromised children.Methods: We employed a descriptive approach to review scientific literature published in English. The literature search was conducted in the PubMed, ScienceDirect, CINAHL, and Google Scholar databases. The review process is illustrated using the PRISMA flow diagram. We present a descriptive summary of the common characteristics of the included studies. The selected articles were analysed and synthesised using a thematic theoretical framework. Results: A total of 16 articles were included in the final analysis. We identified one main theme: the course of COVID-19 in immunocompromised children; two secondary-level themes: (1) children with weakened immunity and COVID-19, and (2) diagnosis and treatment of COVID-19; as well as five primary-level themes.Discussion and conclusion: We found that children with weakened immunity mostly experienced a mild course of COVID-19, with limited data indicating a severe course of illness. These findings emphasise the importance of hygiene measures and the need to monitor the health and well-being of at-risk groups.
Keywords: coronavirus disease; course of infection; immunocompromised children; imunsko kompromitirani otroci; koronavirusna bolezen; potek okužbe